Small Bowel Review: Part II - ABR Thomson; JA Thomson; MJ Ropeleski; GE Wild (Canadian Journal of Gastroenterology)
Major scientific advances have been made over the past few years in the areas of small bowel physiology, pathology, microbiology and clinical sciences. Over 1000 papers have been reviewed and a selective number are considered here. Wherever possible, the clinical relevance of these advances have been identified. Topics discussed are enterocyte proliferation and growth factors; amino acids, peptides and allergies; motility; salt and water absorption and secretion – diarrhea; vitamins and minerals; early development and ageing of the intestine; and ethanol effects.